The Analysis of Performance of Fery Boats Freight Transportation of Tarakan-Sebawang Route North Kalimantan - Bakri, Muhammad Djaya; Azitah, Nur; Syarif, Iif Ahmad; Nawir, Daud; Harwadi, Fuad (Universitas Ibn Khaldun Bogor, 2025)
UPTD Juwata Tarakan Ferry Port has opened crossing services on the Tarakan-Sebawang route (Tana Tidung Regency) since 2021. This research aims to determine the level of crossing services for passengers carrying goods on their journey. The research aims to provide input to managers to improve the quality of service performance. Data was collected through a questionnaire filled out by 70 selected respondents from a number of ferry passengers at the time the survey was conducted. Statistical analysis of questionnaire data using a validity test obtained rcount > rtable, and a reliability test obtained a Cronbach alpha value > 0.70, so the data obtained was valid and reliable. Further analysis using the Customer Service Index method obtained a CSI value of 86.66 with a very satisfactory service category. The results of the Importance Performance Analysis (IPA) method analysis of 19 measurement attributes show that there are two attributes whose performance needs to be improved. Then the results of the Quality Function Deployment (QFD) method analysis provide eight activities that must be carried out, including providing lifeboats, life jackets, marking evacuation routes on ships, qualified officers and sufficient numbers to carry out evacuations and provide services to the passenger.